Motivation in the workplace : inspiring your employees - Banks, Lydia (American Media Pub. West des MoinesUS, 1997)
Explains the nature of employee motivation and examines reasons why persons work, using Maslow's and McClelland's categories of human needs. Identifies values, team vision, rewards, positive work environment, and open communication as some of the factors that affect motivation. Suggests ways to deal with unmotivated workers.